Effect of platelet-rich plasma on dental stem cells derived from human impacted third molars. (January 2011) - Lee, Ui-Lyong; Jeon, Soung Hoo; Park, Joo-Young; Choung, Pill-Hoon
Aim: Platelet-rich plasma (PRP) is fabricated from autologous blood and extensively used to promote soft and hard tissue healing. In the dental field, autologous PRP is widely used combined with dental implant installation and bone graft. This study will evaluate the biologic effect of PRP on the proliferation and the differentiation of human dental stem cells, and find the key cytokines inducing these effects to estimate the clinical feasibility of PRP for dental tissue engineering.Materials & methods: Venous blood was obtained from four individuals and each PRP was fabricated. The human dental stem cells were obtained from the periodontal ligament (PDL) and dental pulp of the surgically extracted human third molars and expanded in vitro . Immunocytochemical staining and flow cytometry with STRO-1 and CD146 confirmed existence of mesenchymal stem cells in the PDL and dental pulp. The effect of PRP on the proliferation of PDL stem cells (PDLSCs) and dental pulp stem cells (DPSCs) was assessed by colony-forming ability measurement, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay and bromodeoxyuridine incorporation assay. Alkaline phosphatase activity and calcium deposit were measured to evaluate the mineralization effect of PRP PDLSCs and DPSCs. Alizarin red S staining was used to detect mineral nodules. Odontogenic and osteogenic gene expressions were evaluated in the PRP-treated PDLSCs and DPSCs by real-time quantitative PCR. A protein array was performed to detect the key cytokines that have an important role in the tissue regenerative effect of PRP.Results: Flow cytometry cell sorting showed that the cells from human PDL and dental pulp contained mesenchymal stem cell populations. Colony-forming ability and cellular proliferation of the dental stem cells were increased at 0.5 and 1% PRP concentration but decreased at 5% concentration. Long-term treatment with 1% PRP enhanced proliferation of the human dental stem cells PDLSCs and DPSCs by 120 h and showed the most significant enhancement at 96 h. PRP also promoted mineralization differentiation of the two kinds of dental stem cells as shown by measurement of alkaline phosphatase activity and calcium deposit under mineralization conditioned media. Increased formation of mineral nodules stained with alizarin red was observed in both PDLSCs and DPSCs after treatment with 1% PRP. Real-time quantitative PCR showed higher odontogenic and osteogenic gene expressions in PRP-treated PDLSCs and DPSCs. RANTES/CCL5 and ICAM-1 were the two key cytokines that were detected in human cytokine array with PRP.Conclusion: The appropriate concentration of the PRP treatment enhanced proliferation and mineralization differentiation of human dental stem cells. RANTES/CCL5 and ICAM-1 might play an important role in PRP-induced tissue regeneration but further study is needed to investigate the whole mechanism.